Pengaruh ROA, CAR, dan NPL terhadap Harga Saham Perbankan di BEI Periode 2020–2024 - Sri Indah; Yuni Setyawati; Elly Lestari; Jumiyati Iwan B tatu (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Stock prices of banking companies are often associated with financial performance indicators that reflect a company’s ability to generate profits, maintain capital adequacy, and manage credit risk. This study aims to analyze the effect of Return on Assets (ROA), Capital Adequacy Ratio (CAR), and Non-Performing Loan (NPL) on stock prices of banking companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach using multiple linear regression analysis. The sample was determined through purposive sampling, resulting in 50 observations, using secondary data obtained from companies’ financial statements.The results indicate that ROA has a positive and significant effect on stock prices, CAR has a negative and significant effect, and NPL has a positive and significant effect on stock prices. These findings suggest that profitability and credit risk are important considerations for investors, while a high level of capital adequacy is not necessarily positively responded to by the market.